CFTR modulator therapies – Effect on life expectancy in people with cystic fibrosis (2020)
CFTR modulators have dramatically changed the clinical course of CF in those fortunate enough to receive them. Inevitably, randomised controlled trials during the development of these drugs are too short to use mortality as an outcome. Evidence for their effect on life expectancy are best gained from real world registry studies specifically looking at mortality, but these are only available for ivacaftor to date. Therefore, indirect evidence must be obtained by looking at outcomes known to affect mortality and seeing the effect of these drugs on those outcomes.